A weight-management camp followed by weekly after-school lifestyle education sessions as an obesity intervention for Qatari children: a prospective cohort study. (13th November 2015) - Taylor, Michael James; Vlaev, Ivo; Taylor, David; Gately, Paul; Ahmedna, Mohamed; Kerkadi, Abdelhamid; Lothian, Jackie; Alsaadi, Aziza; Al-Kuwari, Mohamed; Gholoum, Suhaila; Al-Kuwari, Hanan; Darzi, Ara
Abstract: Background: Weight-management camp interventions for obese children are effective for short-term weight loss. However, there is little evidence indicating how gains made with such interventions can be maintained in the longer term. The present prospective cohort study investigated effectiveness of an intervention consisting of a weight-management camp followed by weekly lifestyle education sessions. Methods: Obese children from eight Qatari schools participated in the intervention from Jan 27 to May 20, 2015. It started with a 2 week weight-management camp involving physical and social activities, lifestyle learning, and dietary control. Participants then attended school as usual for 3 weeks. Ten, weekly after-school club sessions were then held, each lasting 2 h, involving further lifestyle education and engagement of participants' parents, with the aim of encouraging consolidation of learning that had taken place at the camp, and continuation of healthy behaviours. A control group of obese children from the same Qatari schools received no intervention. The primary outcome variable was body-mass index SD scores (BMI SDS). Wilcoxon signed rank tests were used to assess changes in BMI SDS. Informed consent was obtained from participants and their parents. Ethics approval was granted by the Qatar University Institutional Review Board. Findings: 56 children (42 girls) aged 9–13 years (mean 10·9, SD 1·1) took part in the intervention. BMI SDS ranged from 1·17 to 4·00 (mean 2·51, SD 0·62). The control group consisted of 37 children (27 girls) aged 8–12 years (mean 10·3, SD 1·1) with BMI SDS 1·40–3·98 (2·78, 0·43). Between the start of camp and the end of the clubs, there was no significant change in control group BMI SDS (mean −0·004, SD 0·29; p=0·784), but significant reduction in the intervention group BMI SDS (−0·10, 0·20; p=0·0003). Significant BMI SDS reduction occurred for the intervention group during weight-management camp (−0·13, 0·12; p<0·0001) and after-school club (−0·12, 0·19; p<0·0001) stages; significant BMI SDS increase occurred between these stages (0·15, 0·16; p<0·0001). Interpretation: This small-sample study suggests that weekly lifestyle education sessions can be effective in helping to sustain weight-loss achievements from more intensive childhood obesity interventions. Half of the intervention group achieved an overall BMI SDS reduction of at least 0·10, which has been shown to be associated with important reductions in insulin and total cholesterol. Funding: This research was supported by the National Priorities Research Program Qatar Foundation (grant X-036-3–01).